Measuring Customer Satisfaction for Small Cars—An Empirical Study - Suresh, A. M.; Raja, K. G (Indian Journal of Marketing, 2006)
Consumer satisfaction is a growing concern of businesses throughout the world. Increased competition and consumer demand for quality have moved corporations to devote larger portions of their market research budgets to studies of customer satisfaction. Today, manufacturing and service companies, large and small, use satisfaction research to determine the critical product attributes that result in customer satisfaction. This research reports and measures customer satisfaction of small cars in Bangalore city. The research identified sales support, vehicle design, purchase support, cost of ownership and delight features as underlying factors of customer satisfaction. The research tries to rank the small cars on these factors. The study also tries to find out whether customer satisfaction varies among customers on the basis of demographics.